2015
DOI: 10.1021/acs.energyfuels.5b02460
|View full text |Cite
|
Sign up to set email alerts
|

Screening Pathways for the Production of Next Generation Biofuels

Abstract: A large number of alternative fuel molecules based on lignocellulosic biomass have been proposed recently, but a reliable evaluation of their economic potential is challenging due to the limited data available. A rapid screening methodology, Reaction Network Flux Analysis (RNFA), has been suggested to screen a large number of future reaction pathways. The RNFA is extended in this work by a comprehensive sensitivity analysis to account for inevitable uncertainty in the underlying data and hence in the ranking o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 47 publications
1
53
0
2
Order By: Relevance
“…In conclusion, a low lignin content of the feedstock biomass is clearly beneficial for a low carbon loss and low fuel costs. This is in line with earlier studies showing that the production of biofuels derived from lignin is economically not feasible . A low lignin content not only implies an increased fraction of carbohydrates that can be converted effectively to biofuels, but also diminishes the inhibition potential of enzymes during hydrolysis …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In conclusion, a low lignin content of the feedstock biomass is clearly beneficial for a low carbon loss and low fuel costs. This is in line with earlier studies showing that the production of biofuels derived from lignin is economically not feasible . A low lignin content not only implies an increased fraction of carbohydrates that can be converted effectively to biofuels, but also diminishes the inhibition potential of enzymes during hydrolysis …”
Section: Resultssupporting
confidence: 90%
“…This is in line with earlier studies showing that the production of biofuels derived from lignin is economically not feasible. 56 A low lignin content not only implies an increased fraction of carbohydrates that can be converted effectively to biofuels, but also diminishes the inhibition potential of enzymes during hydrolysis. 55 Figure 5(b) shows the screening results for a variation of c/hc ratio at a fixed average lignin content with average pretreatment and hydrolysis yields.…”
Section: Analysis Of Minimal Viable Sugar Yieldmentioning
confidence: 99%
“…[354] 2-n-Butyltetrahydrofuran (2-BTHF) 2-BTHF is aC 8 molecule bearing the THF moiety (boiling point = 160 8 8C; density = 0.86 gcm À3 )and represents apotential fuel additive. [69,317] Thesynthesis of 2-BTHF starting from the platform chemical furfural has been previously reported. In the course of the preparation of n-octane through the dehydration/hydrogenation of furfuralacetone (FFA; see Scheme 6), 2-BTHF was detected as aside product.…”
Section: -Ethyltetrahydrofuran (2-ethf)mentioning
confidence: 99%
“…Thei nteresting properties of this bio-derived molecule,c omparable to gasoline, [241,316] have motivated numerous investigations of its sustainable production. [69,317] 2,5-DMF is generally obtained by hydrogenation/dehydration( or hydrogenolysis) of the platform chemical HMF (Scheme 5). In general, the transformation of C 6 sugars to 2,5-DMF is at wo-step process involving acid-catalyzed isomerization and dehydration of monosaccharides to HMF,f ollowed by hydrogenation/dehydration of the resultant HMF by using av ariety of heterogeneous catalysts.…”
Section: -Methylfuran (2-mf)mentioning
confidence: 99%
“…[2] Recent studies have shown that, based on current production technologies, 6-pentylundecane, 2-methyltetrahydrofuran, and ethyl levulinate are promising next-generation biofuels that could exceed the performance of bioethanol in both cost and environmentali mpact. [3] Furthermore, efficient and precise new ways to produce hydrocarbon, cyclic ether,a nd levulinate biofuels from simple biomass platformc hemicalsm ay drive breakthroughst on ext-generation biofuels. Upgrading strategies to convert platform chemicals into higher molecular weightf uels typicallyc onsist of two or three independent steps:( 1) acid-or base-catalyzed condensation of simple fuelp recursors into carbon-chain-extended complex fuel precursors, (2) hydrogena-tion to cyclic ethers, and/or (3) hydrodeoxygenation (HDO) of ethers to alkanes( Scheme 1a).…”
mentioning
confidence: 99%